Italian Trotskyism and relations with the Fourth International (1945-1953) - Luparello, Velia Sabrina (2024)
The founding conference of the Fourth International held in September 1938 found the Trotskyist movement worldwide in a major organizational crisis that had begun in mid-1930s. Italian Trotskyism did not escape the climate of general crisis. By the beginning of World War II, there was no Italian section of the Fourth International. The need for an Italian party of the IV International became an urgent matter from March 1943. The wave of strikes that began in some cities in northern Italy, followed by the deposition of Mussolini and the rise of the Italian Resistance, put the political situation in this country at the centre of the International Secretariat´s debates. From 1943 to 1948, the official Italian section of the IV International was the Partito Operaio Comunista (Bolscevico-Leninista), yet the late formation of this party and the sectarian politics of the IS made it difficult for the IV International to assess the political situation in Italy. Likewise, the strong political differences between the International Secretariat and the Partito Operaio Comunista prevented the Italian group from having a real insertion in the workers and mass movement.